THE EFFECT OF FASTING DIETS (INTERMITTENT FASTING) ON CHANGES IN BODY WEIGHT AND BODY MASS INDEX (BMI) - Rifatul Masrikhiyah; Anggray Duvita Wahyani (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Intermittent fasting (IF) is gaining popularity as a non-pharmacological intervention for weight loss and the improvement of cardiometabolic profiles. This study aimed to determine the effect of intermittent fasting on changes in body weight and Body Mass Index (BMI) among students at Muhadi Setiabudi University. A pre-experimental design with a one-group pretest-posttest approach was employed. The study sample consisted of 40 respondents whose body weight and BMI were measured before and after the intervention. Data were analyzed using the Paired Sample T-Test. The results showed a decrease in the respondents' mean body weight from 49.31 kg to 48.26 kg and a decrease in mean BMI from 20.85 to 20.40. Bivariate analysis revealed a significance value of 0.000 (p 0.05) for both variables, demonstrating a significant effect of intermittent fasting on reductions in body weight and BMI. The study concludes that intermittent fasting influences changes in the students' body weight and BMI.